SWAT Model Performance on QSWAT Program to Predict Water Discharge in the Upper Citanduy Sub-watershed - Akmal Ikhsan Maulana; Sapei, Asep (Jurnal Teknik Sipil dan Lingkungan, 2025)
The Citanduy Watershed is one of the largest watersheds on Java Island and is in critical condition. The Upper Citanduy Sub-watershed is the main sub-watershed in the Citanduy Watershed, which needs attention because it greatly affects the quantity and quality of its water. The Soil and Water Assessment Tool (SWAT) model, which is a hydrological model developed in the United States, can be used to predict the quantity of water. However, the water balance in the SWAT model uses the water balance for plants planted on dry land (up land) and is less suitable for watersheds that have rice fields (low land). For watersheds that have rice fields, pot hole and modified SWAT features have been tried and developed. This study aims to analyze the performance of the SWAT model with original features, pot hole features, and modified features in the QSWAT program to predict water discharge in the Upper Citanduy Sub-watershed. The results of the study indicate that the modified SWAT has the best performance compared to the original SWAT and pot-hole SWAT, as indicated by the NSE and R2 values. The NSE values of the original SWAT, pot hole SWAT, and modified SWAT were 0.70, 0.73, and 0.75, respectively. The R2 values of the modified SWAT, Original SWAT, and pot hole SWAT were 0.94, 0.93, and 0.94, respectively.